PENGARUH HUMAN RELATION DAN SOLIDARITAS PEGAWAI TERHADAP KUALITAS PELAYANAN PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN DOMPU - Nihra, Nihra; Amirulmukminin, Amirulmukminin (Jurnal Ilmiah Cakrawarti, 2023)
The key to providing better service quality is meeting or exceeding the expectations of the expected service. The way to be able to provide quality service is with employees who have high human relations and solidarity. This study aims to identify and analyze the influence of human relations and employee solidarity on service quality at the Dompu Regency Public Works and Spatial Planning Office. This research is an associative type by taking a Likert scale questionnaire as a research instrument. The study population was 519 with the number of samples taken as many as 126 employees of the Dompu Regency Public Works and Spatial Planning Office with PNS status. Determination of the sample was carried out by purposive sampling technique with the method of collecting observational data, questionnaires and ending with a literature study. Then the data were analyzed using validity, reliability, classic assumption test, multiple regression, correlation, determination and hypothesis testing consisting of t test and f test. The results of the study show that human relations and solidarity simultaneously influence the quality of service at the Dompu Regency Public Works and Spatial Planning Office.